Incidence of Metformin-Induced Lactic Acidosis in Diabetic Patients (Journal of Fatima Jinnah Medical University, 2025)
Background: Metformin is a common treatment for diabetes, yet it poses a risk of lactic acidosis, especially in patients with underlying conditions such as heart failure or liver dysfunction. This study investigates the impact of metformin on lactate levels, evaluates its role as a risk factor for lactic acidosis, and examines key patient characteristics associated with elevated lactate levels.Subjects and methods: This study was a cross sectional study at August 15, 2524 to November 15, 2024 of the occurrence of lactic acidosis in patients treated with metformin at Buriram Hospital. The study tracked outcomes from day 0 to day 90, taken with metformin Abnormal laboratory values ​​(blood lactic acid, blood bicarbonate, blood acidity and kidney function. inclusion criteria for the study sample encompassed patients diagnosed with the following conditions: insulin-dependent diabetes mellitus with ketoacidosis and Blood oxygen level SpO2 is lower than 95%, And study outcome involved 150 diabetic patients, whose creatinine, eGFR, and HbA1c levels were measured before and after receiving standard treatments, including metformin. Lactate levels were assessed using Enzymatic Colorimetric Assay and Biosensor techniques. Blood lactate levels above 4.4 mmol/L were used as a threshold for evaluating lactic acidosis. And analyze the results using t-test by Stata version 14 program.Results: Patients receiving metformin, especially at doses exceeding 2,550 mg/day, exhibited significantly elevated lactate levels (p < 0.001). Elevated lactate was more prevalent among patients with specific conditions, including insulin-dependent diabetes mellitus with ketoacidosis, hypoglycemia, and acute renal failure. Patients treated with glipizide showed statistically significant changes in creatinine and HbA1c levels (p < 0.05), confirming its impact on these parameters.Conclusion: Elevated lactate levels associated with metformin use may indicate a risk of lactic acidosis, particularly in high-risk patient groups or those receiving high doses. Lactate thresholds of 4.4 mmol/L may serve as a diagnostic criterion for lactic acidosis. Close monitoring and tailored dosing of metformin are essential for minimizing risks.
Keywords: Lactate; Lactic acidosis; Metformin; MALA; Glycolysis; Glycogen synthesis